Manual sobre cantos y danzas achuar : propuesta metodológica para octavo y noveno de EGB - Tanchim Yurank, Irarit Esperanza (2018)
This worksheet has been done for students on 8th and 9th grade of Basic General Education. The reason is, actually, young people don’t know nothing about “Anents” (sacred songs), like “forgiveness songs”, “work songs”, “dancing songs”, “hunt songs” among others. This is a real and serious problem when young people get married. Another important reason -to me- it is to recover and encourage all our elderlies’ knowledge, through practice’s experiences the youth could learn without despising its identity. Nowadays, with the occidental’s music, young people fail on studies because they follow what those music says and even “teaches”. Because of these reasons I’ve dedicated this final thesis to the achuar’s apprentices, they could learn from this support material, also could be the same for the teachers on their teaching-apprenticeship process with the students. This text has four units, the first unit, it’s about simple songs, that means they could be sing any moment in the house or work time. The second unit it is about dance’s songs, these ones are specially for family’s parties or social events. The third unit it is about pleadings anent, which are dedicated to husband, wife, son or daughters, when they are far away their native region; and have harmonic feelings. The last unit (forth) it is about forgiveness anent, there are similar to the third one, but they are specially dedicated when adultery its committed, murder or familiar critics. These ones are the stronger Anents, in which people have to do fasting experience.